Study and modelling the respiration of corn seeds (Zea mays L.) during hermetic storage - Marcos Valle, Facundo; Gaston, Analia; Abalone, Rita Mónica; De La Torre, Diego; Castellari, Claudia Carla; Bartosik, Ricardo Enrique (Elsevier, 2021)
The dynamics of oxygen (O2) and carbon dioxide (CO2) concentrations were characterized in corn (Zea mays L.) seed hermetically stored in glass jars at 15, 25 and 35 °C and 14.3, 16.5 and 18.3% moisture content. Gas concentration curves were modeled with linear and exponential correlations and the respiration rate was calculated for each temperature and MC combination as storage time progressed and O2 was consumed. Three predictive respiration models were proposed: Model I, dependent on temperature and MC, and Model IIA, dependent on temperature and oxygen (fitted for each MC level), and Model IIB, dependent on temperature, MC and O2. All models were validated with two independent sets of experimental data. Respiration rate increased with MC and temperature, and it appeared that O2 concentration affected respiration only after a critical limit of about 1% was reached. The values of respiration rates obtained in this study were from 1.36 to 823.76 mg O2 d−1 and from 0.83 to 1265.62 mg CO2 d−1. Respiration rate substantially increased for aw conditions greater than 0.85, presumably due to the onset of the embryo's metabolic activity and the activation of the facultative microorganisms. Literature data was provided to support this observation. Based on this study, Models I and IIB could be indistinctly used in simulation models for predicting O2 and CO2 evolution of hermetically stored seed. However, model IIB provides the advantage of attenuation of the respiration rate as O2 is depleted.